THE INFLUENCE OF FINANCIAL LITERACY AND THE USE OF SOCIAL COMMERCE ON THE FINANCIAL PERFORMANCE OF MSMEs IN MADURA - Sasa Marita Sari; Arie Setyo Dwi Purnomo; Prasetyo Nugroho (Jurnal Manajemen Sains dan Organisasi, 2024)
Objective – The objective of this study is to examine how financial literacy and of social commerce usage affect the financial performance of MSMEs in Madura, concentrating on the function of cashless payment as a moderating factor in the relationship.Design/Methodology/Approach – The collected data for this study through quantitative methods such as interviews and questionnaires from the MSME population in Pamekasan Regency, utilizing the purposive sampling method for sample determination. A structural equation based on partial least squares (PLS) was used to analyze the data model through SmartPLS 4.0 software. PLS calculation using algorithms and bootstrapping.Findings – The study's findings show that there is a positive and significant impact of financial literacy and social commerce usage on the financial performance of MSMEs in Madura. Cashless payment has the capacity to reinforce the impact of financial literacy on the financial performance of MSMEs in Madura, but cashless payment does not have a significant moderation effect or as a moderation homologizer (potential moderation) in the connection between their adoption of social commerce and Madura's MSMEs' financial performance.Conclusion and Implications – Financial performance is favorably and significantly impacted by two factors: financial literacy and the application of social commerce. Meanwhile, the implementation of cashless payment as a moderation variable produces different effects. This cashless payment system has been proven to strengthen the relationship between financial literacy and financial performance; however, it does not have a significant moderation effect or is unable to strengthen or weaken the impact of social commerce on the financial performance of MSMEs in Madura. Keywords: Cashless Payment, Financial Literacy, Financial Performance, Social Commerce